Carcass yields and physiochemical meat quality characteristics of Namibian gemsbok (Oryx gazella) as influenced by muscle, gender and age. (November 2020) - Hoffman, Louwrens C.; van Schalkwyk, Diana L.; Muller, Magdalena; Needham, Tersia; van Rensburg, Berndt J.; McMillin, Kenneth W.
Abstract: The carcass yields and physiochemical meat quality characteristics of six different muscles ( biceps femoris, infraspinatus, longissimus thoracis et lumborum, semimembranosus, semitendinosus, supraspinatus ) for different sex and age groups of gemsbok antelope were determined. No live weight nor dressing percentage differences were observed for the different sex groups. While muscles, age and sex had an influence on the physiochemical parameters investigated, these differences were minor. The CIE Lab colour values for all muscles, age and sexes were in line with those deemed acceptable for game meat, while mean crude protein (20.7%) and fat (1.6%) levels were typical of game species. Discriminant analysis revealed no differentiation among the muscle groups for the variables measured. Thus, at similar live weights, male and female (sub-adult) gemsbok can be considered of equivalent meat quality and marketed accordingly. Highlights: No sexual dimorphism was found for slaughter yield in gemsbok. Age and sex had a minor influence on the physiochemical quality of muscles. Meat surface colour of muscles was within acceptable ranges for game species. Gemsbok muscle crude protein content is high (20.7%) and fat is low (1.6%). Male and female gemsbok meat can be considered of equivalent quality.